Towards a Constructed Wetland/Reservoir- Tank System for Rainwater Harvesting in an Experimental Catchment in Colombia - Galarza Molina, Sandra Lorena (2015)
This paper presents the overview of the Pontificia Universidad Javeriana Bogotá (PUJB) RWH (rainwater harvesting) experience. In Colombia, few researches have developed projects for RWH; and no researches have considered SUDS (Sustainable Urban Drainage Systems) for RWH purposes. The PUJB’s RWH project was a result of a research process that started within the campus in 2007, by the research group Ciencia e Ingeniería del Agua y el Ambiente (from the same university), within the framework of the PUJB Environmental Management Plan and the collaboration of the Physical Resources Office (PRO) of the University. The chosen technology, constructed-wetland/reservoir-tank (CWRT), collects stormwater runoff from a university parking building (3,776 m2), the soccer field and the areas that surround the system (14,816 m2). Recently, a monitoring program focused on the main changes of the stormwater quantity of the system was launched. The first results show that the CWRT fulfils its purpose in terms of peak and volume runoff attenuation. Additionally, the system can be seen as a full-scale laboratory to study the biodiversity and ecological impacts within the hydrological and hydraulic processes too.